Detecting navigation challenges for the visually impaired with mobile monitoring of biosignal - Islam, Mohammad Waseq ul; Tasnim, Ridwana; Bhuiyan, MD. Hasib Ullah (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.